Integrasi Nilai-Nilai Ketuhanan pada Materi Maharah Qira’ah di Prodi Pendidikan Bahasa Arab IAIN Metro - Albarra Sarbaini; Nurwadjah Ahmad Eq; Andewi Suhartini (Institut Agama Islam Negeri (IAIN) Metro, 2021)
This study aims to determine the integration of divine values in maharah qira'ah material in the IAIN Metro Arabic Language Education study program. This type of research is a qualitative-descriptive study, using data collection tools, observation, interviews and documentation. Researchers found that there was an integration of divine values in the maharah qira'ah material which was very helpful in building noble character and morals for students. The reading texts in this material contain some praiseworthy morals, such as faith, honesty, and trust. With the selection of the reading text theme, students not only master the maharah qira'ah but also know the divine values that exist in the qira'ah text, live it up, and implement it into social life.